The steady-state level of plasma membrane ceramide is regulated by neutral sphingomyelinase 2 - Anne G. Ostermeyer-Fay; Abhay Kanodia; Ranjana Pathak; Maria Jose Hernandez-Corbacho; Aarnoud C. van der Spoel; Yusuf A. Hannun; Daniel Canals (Journal of Lipid Research)
During the last 30 years, an increasing number of cellular functions have been reported to be regulated by the lipid ceramide. The diversity in the ceramide structure, leading to tens of ceramide species and the discrete distribution based on subcellular topology, could explain the wide variety of functions attributed to this bioactive lipid. One of these pools of ceramide resides in the plasma membrane, and several works have suggested that an increase in plasma membrane ceramide (PMCer) in response to stimulation leads to cell death and modulates cell adhesion and migration. However, there is a limitation in studying PMCer content in this location primarily due to the inability to quantify its mass. Our group recently developed a method to specifically quantitate PMCer. In this work, we interrogate what sphingolipid metabolizing enzymes are responsible for modulating the basal levels of plasma membrane ceramide. An in-silico prediction and experimental confirmation found an almost perfect correlation between the endogenous expression levels of neutral sphingomyelinase (nSMase2) and the amount of plasma membrane ceramide in unstimulated cells. Manipulating the expression levels of nSMase2, but not other candidate enzymes of ceramide metabolism, profoundly affected PMCer. Moreover, a physiologic induction of nSMase2 during cell confluence resulted in a nSMase2-dependent dramatic increase in PMCer. Together, these results identify nSMase2 as the primary enzyme to regulate plasma membrane ceramide.